2008
DOI: 10.1007/s10620-008-0377-9
|View full text |Cite
|
Sign up to set email alerts
|

Partially Hydrolyzed Guar Gum Attenuates the Severity of Pouchitis in a Rat Model of Ileal J Pouch-Anal Anastomosis

Abstract: We aimed to evaluate the efficacy of treatment with partially hydrolyzed guar gum (PHGG) using a rat model of ileal pouch-anal anastomosis and pouchitis. In the J pouch groups, tissue myeloperoxidase activities were significantly higher than native myeloperoxidase activities (P = 0.020; P = 0.015; P = 0.004, respectively). A statistically significant difference in total histological score was detected in the J pouch + 5% dextran sulfate sodium (DSS) group, compared to the J pouch control and the J pouch + 5% D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The ameliorative effects of PHGG on IBD, which includes conditions such as CD (8), UC (29), and IBS (30,31), are well demonstrated in animal experimental models. In 1994, a study in nine healthy Japanese men who were administered soluble dietary fiber (7 g at each meal for 2 weeks) reported that the percentage of fecal bifidobacterial increased with fiber intake, but returned to normal when the intake was stopped (6).…”
Section: Discussionmentioning
confidence: 94%
“…The ameliorative effects of PHGG on IBD, which includes conditions such as CD (8), UC (29), and IBS (30,31), are well demonstrated in animal experimental models. In 1994, a study in nine healthy Japanese men who were administered soluble dietary fiber (7 g at each meal for 2 weeks) reported that the percentage of fecal bifidobacterial increased with fiber intake, but returned to normal when the intake was stopped (6).…”
Section: Discussionmentioning
confidence: 94%
“…These models allow for the reconstruction of surgical procedures in humans but they are relatively rarely used due to their sizes and related costs, as well as other restrictions,. Rat models are used much more frequently [12,13], in which either idiopathic pouchitis is assessed [14] or it is chemically induced, most frequently with the use of 5% dextran sulfate sodium (DSS) [15], iodoacetamide or dinitrobenzene sulfonic acid (DNBS) [16]. The rat experimental models of pouchitis pose a vast array of surgical difficulties related to the necessity of the performance of a low anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pouch specimens were assessed according to the criteria described by Atila et al[16]. Erosion was evaluated as: 0, negative; 1, focal erosion; 2, erosion in many regions; or 3, extensive erosion.…”
Section: Methodsmentioning
confidence: 99%